1995
DOI: 10.1113/jphysiol.1995.sp021009
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenesis associated with spontaneous activity: an important component of thermoregulatory needs in rats.

Abstract: 1. Quantification of the energy cost of spontaneous activity in freely moving lean and obeseZucker rats was performed at 28°C and during acute cold exposure (from 28 to 5°C).2. An open-circuit metabolic chamber was supplemented with an ultrasensitive ergometric platform equipped with six unidirectional accelerometers and with an opto-electronic device for location of the rat's centre of mass. 3. Resting and mean metabolic rates during control and cold-exposure periods were similar in both groups of rats. The '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…Morrison [27] first demonstrated that SPA in rodents accounted for 25% of total energy expenditure, the magnitude of which was later confirmed by Brown et al [28] and Girardier et al [29]. These findings in rodents parallel data from human studies demonstrating the significant impact of SPA-induced energy expenditure on total energy expenditure [9, 16, 30].…”
Section: Physiological Significance Of Spa and Neat To Energy Balancementioning
confidence: 85%
See 1 more Smart Citation
“…Morrison [27] first demonstrated that SPA in rodents accounted for 25% of total energy expenditure, the magnitude of which was later confirmed by Brown et al [28] and Girardier et al [29]. These findings in rodents parallel data from human studies demonstrating the significant impact of SPA-induced energy expenditure on total energy expenditure [9, 16, 30].…”
Section: Physiological Significance Of Spa and Neat To Energy Balancementioning
confidence: 85%
“…These SPA differences were maintained independent of diet-induced changes in body weight [36]. Likewise, lean rats have greater SPA and SPA-induced energy expenditure compared to obese Zucker rats [29]. Similar relationships between body weight and SPA have been observed in Wistar versus hypoactive Wistar-Kyoto rats [37].…”
Section: Physiological Significance Of Spa and Neat To Energy Balancementioning
confidence: 89%
“…This is evident from the fact that young adult (7-10 week-old) Zucker fa/fa rats are capable of mounting vivid thermogenic responses to short-term cold exposure [127][128][129], in spite of their irresponsiveness to leptin. Only at an older age (> 10 week-old) do Zucker fa/fa rats display attenuation of acute thermogenic responses, but such an attenuation coincides with involution of the brown adipose tissue [130].…”
Section: Leptin and Thermoregulation In The Absence Of Inflammationmentioning
confidence: 99%
“…The answer to this question is probably negative for two reasons. First, whereas fever is brought about by acute activation of thermoeffectors [103], leptin appears to be unimportant for acute activation of thermogenesis [127][128][129]. Second, the febrile response to LPS is least manifest [133][134][135][136] under the condition (negative energy balance) that is most propitious for activation of thermogenesis by a rise in circulating leptin [56][57][58]60,62].…”
Section: Role Of Leptin In the Fever And Hypothermia Of Systemic Inflmentioning
confidence: 99%
“…The efficiency of muscular contraction during exercise is low (~25%), but that of spontaneous physical activity (SPA) (including fidgeting, muscle tone and posture maintenance, and other low-level physical activities of everyday life) is even lower since these essentially involuntary activities comprise a larger proportion of isometric work which is simply thermogenic. Because actual work done on the environment during SPA is very small compared to the total energy spent on such activities, the energy cost associated with SPA has been referred to as movement-associated thermogenesis or SPA-associated thermogenesis [8]. It can also be argued that since SPA is essentially beyond voluntary control, a change in the level or amount of such involuntary SPA in a direction that defends body weight also constitute autoregulatory changes in energy expenditure.…”
Section: What Constitutes Adaptive Thermogenesis?mentioning
confidence: 99%